2014
DOI: 10.1155/2014/850367
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Acupuncture in Reducing Preoperative Anxiety: A Meta‐Analysis

Abstract: Background. Acupuncture has been shown to reduce preoperative anxiety in several previous randomized controlled trials (RCTs). In order to assess the preoperative anxiolytic efficacy of acupuncture therapy, this study conducted a meta-analysis of an array of appropriate studies. Methods. Four electronic databases (MEDLINE, EMBASE, CENTRAL, and CINAHL) were searched up to February 2014. In the meta-analysis data were included from RCT studies in which groups receiving preoperative acupuncture treatment were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…An embedded acupuncture technique for preoperative anxiolysis suggested in a recent systematic review13 will be applied to the bilateral acupuncture points of Liver (LI4), Heart 7 (HT7), Stomach (ST36), Yin-Tang, ear Shen-Men and ear sympathetic using the superficial needle (Dongbang Press Needles, 0.18×1.3 mm, Dongbang) the day before surgery and will be removed at the first session of acupuncture on the day of surgery. These treatments will be applied only to the patients in the Acupuncture group.…”
Section: Methods and Analysismentioning
confidence: 99%
“…An embedded acupuncture technique for preoperative anxiolysis suggested in a recent systematic review13 will be applied to the bilateral acupuncture points of Liver (LI4), Heart 7 (HT7), Stomach (ST36), Yin-Tang, ear Shen-Men and ear sympathetic using the superficial needle (Dongbang Press Needles, 0.18×1.3 mm, Dongbang) the day before surgery and will be removed at the first session of acupuncture on the day of surgery. These treatments will be applied only to the patients in the Acupuncture group.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Median APAISa level in the acupuncture group, but not in the control group: 10 (6-13 [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]) to 7 (4-10 [4-18]), p < 0.001 vs. 9 (6-13 [4-18]) to 8.5 (6-12 [4-18]), p = 0.872, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Pilot study data from neurosurgical patients in our institution found a mean (SD) pre-operative STAI-S6 score of 29.5 (14.7). Previous work has suggested that acupuncture may reduce anxiety levels by 25-37%, with a recent meta-analysis considering a 30% reduction in STAI-S6 score to be clinically significant [14]. In order to demonstrate a 30% reduction in STAI-S6 score with 90% power and 5% level of significance, we required 58 patients in each group.…”
Section: Methodsmentioning
confidence: 99%
“…56,57 The effectiveness of acupuncture for treating anxiety has been well documented. [58][59][60] Rather than using acupuncture needles, EFT relies on the manual stimulation of the acupoints. A recent meta-analysis indicated that interventions using acupoint stimulation had a moderate effect size (Hedge's g = -0.66 95% CI [-0.99, -0.33]) in reducing symptoms.…”
Section: Methodsmentioning
confidence: 99%